The Importance of Defence Intelligence Agencies in Non-Combat Military Missions: Instruments of Special Attention for Defence Capacity Building and Capabilities - Arbani, Muhammad (Advances In Social Humanities Research, 2024)
The post-Cold War era has indeed reshaped the security paradigm, witnessing a surge in non-traditional security issues that intersect with military security concerns. The human security approach has expanded the understanding of threats to encompass phenomena like terrorism, climate change, and human trafficking. While Southeast Asia serves as a microcosm of these complexities, it's imperative not to overlook broader global security trends and perspectives. In this region, intricate security dynamics are shaped by diverse factors, including economic downturns, territorial disputes, and environmental shifts. Although non-traditional threats have gained prominence, traditional ones, such as tensions in the South China Sea, persist and demand attention. Countries like Indonesia and the Philippines have responded by bolstering their defence budgets. Moreover, there's a discernible uptick in the adoption of military operations other than war (OMSP), with a growing emphasis on humanitarian aid and disaster relief efforts. However, amidst evolving international strategic landscapes, it's crucial to adapt. For instance, Indonesia's recent establishment of the Defence Intelligence Agency underscores the imperative to enhance defence capabilities for non-war military missions.